(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Phraseological units constitute an essential component of every language, reflecting the interaction between linguistic structure, cultural traditions, and cognitive perception. Among them, phraseological units containing flora and fauna components are particularly significant because they preserve cultural knowledge and metaphorical conceptualizations accumulated throughout generations. This study investigates the structural, semantic, and cultural characteristics of flora- and fauna-based phraseological units in English and Uzbek through a comparative analysis of Kenneth Grahame’s The Wind in the Willows (1908) and Gafur Gulom’s Shum bola (1936). The research applies an integrated semantic–structural–cultural analytical framework grounded in phraseology, cognitive linguistics, and comparative linguistics. The findings demonstrate that both languages share universal cognitive metaphors such as HUMAN BEHAVIOR IS ANIMAL BEHAVIOR and LIFE IS A GROWTH PROCESS. However, significant differences emerge in cultural symbolism, phraseological realization, and evaluative functions. The study reveals three degrees of equivalence—full, partial, and zero equivalence—between English and Uzbek phraseological units. The results contribute to the understanding of phraseology as a multidimensional phenomenon connecting language, cognition, and culture.